O coordenador pedagógico e suas ações na Rede Estadual de Educação do Pará no Município de Altamira - RODRIGUES, Daiane Leite Velozo (2023)
This article is dedicated to analyzing the following question: what does the law say and what is the reality of the role of pedagogical coordination in the state education network in the municipality of Altamira? The specific objectives are: to identify and describ the activities carried out by the pedagogical coordinators and their influence on the students' teaching and learning process, to know the context of the pedagogical coordinator's work and their actions within the scope of state schools in the municipality of Altamira. In the research that gave rise to this writing, document analysis was used as a data collection instrument, which includes documents in the broad sense, not only printed documents, but also photos, magazines, recordings, official institutional documents, among others. In this study, normative documents such as: the Federal Constitution of 1988, the Law of Guidelines and Bases of National Education 9.3940/1996, the National Education Plan 2014/024, the State Education Plan, the School Regulations and the Pedagogical Political Project were analyzed. Considering the objective of this article, it was verified that the normative documents, as the current ones, do not have clarity of reading, that is, the terms were not explicit being these confusing and similar to the verification of the attributions provided to the pedagogical coordinator were not specifically distinguished. In addition, it concludes by emphasizing its importance in the development of school management, in the lives of students and the school community.